Identification of a Novel lincRNA-p21-miR-181b-PTEN Signaling Cascade in Liver Fibrosis - Fujun Yu; Zhongqiu Lu; Bicheng Chen; Peihong Dong; Jianjian Zheng (Mediators of Inflammation)
Previously, we found that long intergenic noncoding RNA-p21 (lincRNA-p21) inhibits hepatic stellate cell (HSC) activation and liver fibrosis via p21. However, the underlying mechanism of the antifibrotic role of lincRNA-p21 in liver fibrosis remains largely unknown. Here, we found that lincRNA-p21 expression was significantly downregulated during liver fibrosis. In LX-2 cells, the reduction of lincRNA-p21 induced by TGF-β1 was in a dose- and time-dependent manner. lincRNA-p21 expression was reduced in liver tissues from patients with liver cirrhosis when compared with that of healthy controls. Notably, lincRNA-p21 overexpression contributed to the suppression of HSC activation. lincRNA-p21 suppressed HSC proliferation and induced a significant reduction in α-SMA and type I collagen. All these effects induced by lincRNA-p21 were blocked down by the loss of PTEN, suggesting that lincRNA-p21 suppressed HSC activation via PTEN. Further study demonstrated that microRNA-181b (miR-181b) was involved in the effects of lincRNA-p21 on HSC activation. The effects of lincRNA-p21 on PTEN expression and HSC activation were inhibited by miR-181b mimics. We demonstrated that lincRNA-p21 enhanced PTEN expression by competitively binding miR-181b. In conclusion, our results disclose a novel lincRNA-p21-miR-181b-PTEN signaling cascade in liver fibrosis and suggest lincRNA-p21 as a promising molecular target for antifibrosis therapy.